Physiological ischemic training improves cardiac function through the attenuation of cardiomyocyte apoptosis and the activation of the vagus nerve in chronic heart failure - Zhu, Xiuhua; Wang, Shenrui; Cheng, Yihui; Gu, Hongmei; Zhang, Xiu; Teng, Meiling; Zhang, Yingjie; Wang, Jiayue; Hua, Wenjie; Lu, Xiao (Frontiers in Neuroscience, 2023)
Purpose This study investigated the functional outcomes of patients with chronic heart failure (CHF) after physiological ischemic training (PIT), identified the optimal PIT protocol, evaluated its cardioprotective effects and explored the underlying neural mechanisms. Methods Patients with CHF were randomly divided into experimental group (n=25, PIT intervention+regular treatment) and control group (n=25, regular treatment). The outcomes included the left ventricular ejection fraction (LVEF), brain natriuretic peptide (BNP) and cardiopulmonary parameters. LVEF and cardiac biomarkers in CHF rats after various PIT treatments (different in intensity, frequency, and course of treatment) were measured to identify the optimal PIT protocol. The effect of PIT on cardiomyocyte programmed cell death was investigated by western blot, flow cytometry and fluorescent staining. The neural mechanism involved in PIT-induced cardioprotective effect was assessed by stimulation of the vagus nerve and muscarinic M2 receptor in CHF rats. Results LVEF and VO2max increased while BNP decreased in patients subjected to PIT. The optimal PIT protocol in CHF rats was composed of five cycles of 5 min ischemia followed by 5 min reperfusion on remote limbs for eight weeks. LVEF and cardiac biomarker levels were significantly improved, and cardiomyocyte apoptosis was inhibited. However, these cardioprotective effects disappeared after subjecting CHF rats to vagotomy or muscarinic M2 receptor inhibition. Conclusion PIT improved functional outcomes in CHF patients. The optimal PIT protocol required appropriate intensity, reasonable frequency, and adequate treatment course. Under these conditions, improvement of cardiac function in CHF was confirmed through cardiomyocyte apoptosis reduction and vagus nerve activation.